Business and Entrepreneur Context of Content Creator - Rihfenti Ernayani; Amiruddin Hamzah; Gerdha Erlinda Sari Lapoliwa; Asep Saepudin; Lucky Radi Rinandiyana (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Digital content has been part in our life as we mostly spend time with our smartphone. Started from seeing recommendation to purchase something, to see latest news, to gain more information, and to expand their thought. Content Creator isn’t mere content anymore when they reach bigger audience and able to perform product promotion. This includes a fact that content creator can construct the reality around their audience. Deddy Corbuzier has this feat and capacity in his content making report and his capacity of inviting government leaders created new perception of intelligence. This means that the era of content can be as bold as academy.